Comparative study of Polish and Dutch meat industry exports with the example of top Polish meat exporters exploiting international opportunities - Ireneusz Janiuk; Mirosław Jarosiński; Natalia Ribberink (International Entrepreneurship Review, 2016)
Today’s world is more and more interconnected and so is its economy. This is especially visible on the example of EU meat industry which accounts for more than 16% of the total meat production and around 15% of the meat trade worldwide. The paper presents meat industry exports from the Netherlands and Poland, both countries ranked among 10 top exporters of meat in EU and not only, and the interconnectedness of the industry in these two countries. A comparative analysis of meat industry composition and export activities in the Netherlands and Poland shows a lot of similarities and allows for identification of push factors that drive internationalisation of meat producers in both countries. This is a starting point for in-depth analysis of how two leading Polish meat exporters, GK Sokołów S.A. and Farmutil S.A., exploit international opportunities.